Nadzór ubezpieczeniowy w skonsolidowanym systemie nadzoru finansowego - Lament, Marzanna (Insurance Supervision in Integrated Financial Supervision, 2008)
The insurance supervision is currently one of integral elements of supervision over financial market. The merger of supervisory activity results from overlapping global process which pertinent to associate with insurance and bank business, increasing complexity of financial products and their distribution channels. Altogether we deal with increasing complexity of insurance products and with new risks, which accompany to insurance business and result largely from pervading of different kind of financial institutions. The merging the supervision over the financial institutions seems well-founded because it allows the insurance system to monitor market more efficiently and to ensure its stability, security and transparency. It is worth to point out that there are different models of supervision over financial market and different solutions regarding organizations of insurance supervision in consolidated financial supervision system. These differences were presented on the example of insurance supervision of Great Britain, Germany and France.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 197-204